2012
DOI: 10.1002/smj.2012
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling market incumbency from organizational prehistory: Locating the real sources of competitive advantage in R&D for radical innovation

Abstract: The creative destruction literature has argued that differences in R&D performance of incumbent vs. entrant firms can be explained through organizational change theories about established vs. de novo firms. A disconnect exists between these theories and the available empirical evidence because often the best performing firms are established firms as well. I propose to resolve this disconnect by distinguishing between market incumbency (presence in a market prior to a discontinuity) and organizational prehistor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Traditionally, first‐mover enterprises participating in GVCs have as their priority to obtain advanced technology and generate excessive profit, so achieving the export competitive advantage in GVCs (Bao & Chen, ; Mathews, ; Suarez & Lanzolla, ; Vecchiato, ), while latecomer enterprises have to face entry barriers erected by first‐mover enterprises. Furthermore, first‐mover enterprises participating in GVCs could forge good relationships with MNCs depending on their “incumbency advantage”, and then obtain effective market information (e.g., product order, product price, and customer profile) in time, reducing trade risk caused by asymmetric information (Alpert & Kamins, ; Lourdes, ; Niedrich & Swain, ).…”
Section: Literature Review and Theoretical Mechanismsmentioning
confidence: 99%
“…Traditionally, first‐mover enterprises participating in GVCs have as their priority to obtain advanced technology and generate excessive profit, so achieving the export competitive advantage in GVCs (Bao & Chen, ; Mathews, ; Suarez & Lanzolla, ; Vecchiato, ), while latecomer enterprises have to face entry barriers erected by first‐mover enterprises. Furthermore, first‐mover enterprises participating in GVCs could forge good relationships with MNCs depending on their “incumbency advantage”, and then obtain effective market information (e.g., product order, product price, and customer profile) in time, reducing trade risk caused by asymmetric information (Alpert & Kamins, ; Lourdes, ; Niedrich & Swain, ).…”
Section: Literature Review and Theoretical Mechanismsmentioning
confidence: 99%
“…Ettlie (2000) considered that in the current environment of continuously changing technology, integrating the innovation of management technology has become the key to modern enterprises' building lasting competitiveness. Lourdes (2013) showed that in the era of the knowledge economy, business development and competitive advantage depend more on enterprises' innovation abilities. Competitive advantage depends primarily on business technology and management advantages, and as such, the competition among enterprises is the competition between their innovation abilities, i.e.…”
Section: Exploring the Positive Impact Of Innovativeness On Competitive Advantage Among Night Market Vendorsmentioning
confidence: 99%
“…Resource‐based theories point to inadequacies in financial, human, and social capital as handicapping startups from scaling and adapting to challenges (Fern et al, 2012). Organizational ecology studies underscore the significance of strategic choices and competitive positioning in determining mortality rates (Lourdes Sosa, 2012). Behavioral research also indicates biases and heuristics among founders that hamper objective decision making (Casti, 2021; Joseph et al, 2021; Onan, 2023b).…”
Section: Research Backgroundmentioning
confidence: 99%